2008
DOI: 10.1158/1541-7786.mcr-08-0042
|View full text |Cite
|
Sign up to set email alerts
|

Cross-talk between Aryl Hydrocarbon Receptor and Mitogen-Activated Protein Kinase Signaling Pathway in Liver Cancer through c-raf Transcriptional Regulation

Abstract: c-raf is a serine-threonine kinase and a downstream effector of ras signaling.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…The mechanism underlying the LPS-induced cross-talk between Ahr and Sp1, however, remains to be investigated in detail. Recent studies have demonstrated cross-talk between the Ahr signaling pathway and MAP kinase pathways (43,44). As MAPKs have been shown to play an important role in Sp1 activation downstream of LPS signaling (45), these reports lead us to hypothesize that the cross-talk between Sp1 and Ahr may be mediated by MAPK activation.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism underlying the LPS-induced cross-talk between Ahr and Sp1, however, remains to be investigated in detail. Recent studies have demonstrated cross-talk between the Ahr signaling pathway and MAP kinase pathways (43,44). As MAPKs have been shown to play an important role in Sp1 activation downstream of LPS signaling (45), these reports lead us to hypothesize that the cross-talk between Sp1 and Ahr may be mediated by MAPK activation.…”
Section: Discussionmentioning
confidence: 99%
“…Disruption of the cellular functions of AHR is also associated with the expression of various diseases, including HCC [25]. The underlying regulatory mechanisms of tumorigenesis remain unclear.…”
Section: Resultsmentioning
confidence: 99%
“…The most significantly enriched canonical pathway was the Aryl Hydrocarbon Receptor Signaling pathway (AHR pathway, p < 3.0 × 10 −6 ), which belongs to the basic helix-loop-helix/Per-Arnt-Sim family of transcription factors (Figure 2 B). This pathway has been reported to regulate xenobiotic metabolizing enzymes such as cytochrome P450 and has been demonstrated to cross-talk with the MAPK pathway [ 25 , 26 ]. Recent studies revealed that the AHR pathway is involved in various signaling pathways that are critical to cell proliferation and differentiation, gene regulation, cell motility and migration, and inflammation [ 27 , 28 ].…”
Section: Resultsmentioning
confidence: 99%